Ultra-slow tails of sprite-associated lightning flashes - Fraser-Smith, Antony C., author; Füllekrug, Martin, author; Reising, Steven C., author; American Geophysical Union, publisher (Colorado State University. Libraries, 1998)
We describe the terrestrial excitation of horizontal magnetic field variations in the Pc1 frequency range (0.2-5.0 Hz) by tropospheric, sprite-associated lightning flashes, measured ~1900 km west from the source. These variations, which we call ultra-slow tails, exhibit amplitudes on the order of tens of pT, they have a duration of ~3 seconds, and they occur immediately following the initial pulse of the sprite-associated lightning flash. The ultra-slow tails exhibit two peaks In the frequency domain at 0.67 Hz and 1.67 Hz: The mean polarization ellipses at these two frequencies are oriented ~45° clockwise from geographic north and exhibit right-hand and left-hand polarization respectively with a weak ellipticity of ~0.1. The horizontal magnetic intensity of the initial pulse is related to the horizontal magnetic intensity of the ultra-slow tail, in agreement with the interpretation of ultra-slow tails as ionospheric Alfven resonances.